2008
DOI: 10.1172/jci31811
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathogenesis of emphysema

Abstract: Emphysema is one manifestation of a group of chronic, obstructive, and frequently progressive destructive lung diseases. Cigarette smoking and air pollution are the main causes of emphysema in humans, and cigarette smoking causes emphysema in rodents. This review examines the concept of a homeostatically active lung structure maintenance program that, when attacked by proteases and oxidants, leads to the loss of alveolar septal cells and airspace enlargement. Inflammatory and noninflammatory mechanisms of dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
184
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(201 citation statements)
references
References 95 publications
11
184
1
5
Order By: Relevance
“…Our results point out that bisphosphonate strongly impacts senescent phenotype reinforcing a potential functional link between bone fragility during aging and increase cellular senescence. It has also been reported that bisphosphonates can impact bone‐independent marks of aging like emphysema (Ueno et al, 2015), emphysema being thought to be regulated by cellular senescence (Taraseviciene‐Stewart, & Voelkel, 2008), further suggesting that FDPS/bisphosphonates can regulate cellular senescence and aging beyond their well‐known bone effects.…”
Section: Discussionmentioning
confidence: 97%
“…Our results point out that bisphosphonate strongly impacts senescent phenotype reinforcing a potential functional link between bone fragility during aging and increase cellular senescence. It has also been reported that bisphosphonates can impact bone‐independent marks of aging like emphysema (Ueno et al, 2015), emphysema being thought to be regulated by cellular senescence (Taraseviciene‐Stewart, & Voelkel, 2008), further suggesting that FDPS/bisphosphonates can regulate cellular senescence and aging beyond their well‐known bone effects.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to emphysema, COPD is frequently associated with an increased number of alveolar inflammatory cells (Taraseviciene‐Stewart & Voelkel, 2008), and PPE‐induced emphysema also causes alveolar inflammation (Houghton et al, 2006). In the PPE‐induced emphysema model, elastin fragments produced by PPE increase macrophage numbers, which secrete elastolytic enzymes such as MMPs (Houghton et al, 2006; Hunninghake et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Because mounting evidence suggests that the apoptotic machinery is also necessary to generate an emphysema phenotype (64,(67)(68)(69), an alternative and potentially complementary hypothesis to explain host susceptibility to the injurious effects of chronic smoke exposure has evolved. This hypothesis suggests that CS-induced alveolar destruction could be exacerbated by abnormalities in pathways critical for lung development and postnatal lung homeostasis, creating an imbalance between cellular programs regulating lung injury and repair (69,70).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis suggests that CS-induced alveolar destruction could be exacerbated by abnormalities in pathways critical for lung development and postnatal lung homeostasis, creating an imbalance between cellular programs regulating lung injury and repair (69,70). Several lines of investigation have supported a role for the disruption of alveolar structural maintenance in the pathogenesis of emphysema.…”
Section: Discussionmentioning
confidence: 99%